The influence of learners' rights and obligations on ill-discipline in schools - Makhubele, Helani Harry (My University, 2015)
This dissertation presents a study on the influence of learners' rights and obligations on ill-discipline in schools in the Man'ombe Circuit. Ill-discipline in educational institutions has become the "buzzword" in the Limpopo Province because of the ill discipline of learners in the schools. Very few schools have good discipline which is conducive to effective learning. Many learners are forced to repeat classes and move from one school to another because of poor discipline. The aim of the study is to investigate the influence of learners' rights on ill-discipline in schools. The following objectives were formulated to assist in the realisation of the aim of the study to investigating the nature of learners' rights, the nature of learner discipline, how learner discipline in the Man'ombe Circuit schools is currently managed and to recommending how learner discipline in the in the schools can be better managed. In the light of the aims of this research, a literature review was used to investigate the influence of learners' rights and obligations on ill-discipline in schools in the Man'ombe Circuit. The literature review consisted of a wide review of relevant writings such as the latest articles, journals, major books on the subject, monographs and dissertations published nationally and internationally. The study was descriptive and therefore used a quantitative method to establish the influence of learners' rights and obligations on ill-discipline in schools in the Man'ombe Circuit. The empirical component of the research was conducted by means of questionnaires in which the educators participated. The aim of administering the administering questionnaires was to investigate the influence of learners' rights and obligations on ill-discipline in schools in the Man'ombe Circuit. The findings of the study are: • The results of the empirical investigation revealed that a major challenge which contributes to ill-discipline in the schools is learners' rights. • It can therefore be emphasized that this study reveals that the learners' rights are responsible for the poor discipline in Man'ombe Circuit schools. The recommendations of the study were: Finally, the researcher gave recommendations for improving discipline in the schools and the suggestions for future research.
MPM
Oliver Tambo Institute of of Governance and Policy Studies
Keywords: Learners; UCTD; Rights; Ill-discipline; Schools; 371.542096825; Corporal punishment -- South Africa -- Limpopo; School discipline -- South Africa -- Limpopo; Punishment -- South Africa -- Limpopo